Hepatitis C virus NS3 helicase contributes to (−) strand RNA synthesis - Ralfs, Philipp; Bressanelli, Stéphane; Günter, Lina M.; Gabel, Alexander; Rothhaar, Paul; Price, Kyle J.; Tubiana, Thibault; Munschauer, Mathias; Frick, David N.; Lohmann, Volker (Nature Communications, 2025)
Many positive strand RNA viruses encode helicases, but their distinct functions in viral replication cycles is poorly understood. Here, we identify a mutation in the helicase domain of HCV non-structural protein 3 (NS3h), D1467G, which specifically affects (−) strand synthesis, phenocopying mutations in the 3’ untranslated region of the genome. D1467G does not impair helicase activity in vitro or the binding of NS3h to critical cis-acting RNA elements, but reduces the interaction of NS3h and NS5B polymerase, potentially contributing to defective (−) strand synthesis. AlphaFold predictions of complexes between NS3h, RNA and/or NS5B suggest that NS3h both remodels the cis-acting RNA elements and unwinds the terminal stem-loop of the HCV genome rendering the template accessible for de novo initiation of (−) strand synthesis by NS5B. Overall, our study provides evidence for a defined function of a viral helicase in (−) strand genome synthesis of a positive strand RNA virus.
Gesehen am 03.02.2026